Manajemen Strategi Dinas Pemberdayaan Perempuan Dan Perlindungan Anak (DP3A) Kota Bandar Lampung Dalam Penanganan Kasus Kekerasan Pada Anak Di Kota Bandar Lampung - Gilang Febriansyah; Andri Marta; Azis Ahmad (Journal of Social Contemplativa, 2026)
Violence against children remains a serious social issue requiring significant attention from local governments. Data indicate that child violence cases in Bandar Lampung City have increased over recent years, particularly sexual violence cases. This study aims to analyze the strategic management of the Women's Empowerment and Child Protection Agency (DP3A) of Bandar Lampung City in handling child violence cases. The study employs a descriptive qualitative approach using Fred R. David's strategic management framework, consisting of strategy formulation, strategy implementation, and strategy evaluation. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that strategy formulation has been relatively effective through the development of programs aligned with national and local regulations as well as child protection needs. However, strategy implementation remains suboptimal due to limitations in human resources, infrastructure, and inter-agency coordination. Furthermore, strategy evaluation primarily focuses on administrative aspects and has not adequately measured substantive impacts on reducing child violence cases. The study concludes that strengthening implementation and evaluation mechanisms is essential to improve the effectiveness of DP3A's strategic management in achieving child protection objectives.